Teacher’s Proactive Approaches to Classroom Behavioral Management: Implications to Guidance Program - Singian, Saturnino (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined teachers’ proactive approaches to classroom behavioral management and their implications for a guidance program. Guided by Coombs’ Systems Approach using the input-process-output model, the study focused on teacher profiles, students’ behavioral problems, factors causing such problems, classroom management approaches, and guidance program implications. A descriptive research design was employed among 50 public elementary school teachers from Cabanatuan City during the school year 2024–2025. The respondents were selected through simple random sampling, and data were gathered using a validated questionnaire adapted from a previous study. Frequency, percentage, weighted mean, and related statistical procedures were used to analyze the responses. Findings showed that most respondents were female, aged 31–40, married, with master’s units, holding Teacher I positions, with 6–10 years of service, handling mostly Grade VI learners, and having attended only one to two training sessions. Teachers strongly agreed that students’ behavioral problems, including vandalism, absenteeism, bullying, technology misuse, inattention, disrespect, cheating, and lack of learning skills, were serious classroom concerns. They also strongly agreed that these problems were influenced by inadequate values education, social media and technology, weak parental guidance, poverty, peer influence, and inconsistent discipline. Teachers strongly supported proactive, student-centered, and non-punitive strategies, particularly supportive school culture, parent collaboration, respectful guidance, emotional regulation, and clear expectations. The study aligns with SDG 4, SDG 3, SDG 16, and SDG 17 by promoting quality education, student well-being, safe school environments, and stakeholder collaboration. Its sustainability impact lies in strengthening educational, institutional, social, and community-based support systems for positive student behavior and effective classroom management.
Keywords: Behavioral Problems; Classroom Behavioral Management; Elementary Teachers; Guidance Program; Students Behavior; Proactive Approaches; School Discipline; Teacher Strategies; Values Education; Positive Discipline